WORKSHOP DAN MONITORING SEBAGAI UPAYA UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MELAKSANAKAN PROSES PEMBELAJARAN DENGAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DI SMK BINAAN PADA SEMESTER GANJIL TAHUN PELAJARAN 2022/2023 - I Wayan Darmasuita (Daiwi Widya, 2022)
AbstractThis research is a School Action Research which aimed at finding out whether workshops and monitoring can improve teachers’ abilities in carrying out the learning process using project-based learning model. The subjects of this study were teachers at the researcher’s assisted vocational schools, namely SMK Negeri 1 Sukasada, SMK Negeri 2 Singaraja dan SMKS Pariwisata Singaraja, totaling 15 people. The method used to collect data was observation using observation sheets. The data analysis method used was descriptive analysis. This research was conducted in two cycles. Each cycle was carried out based on the stages: (1) preparing an activity plan, (2) carrying out actions, (3) observing, and (4) analyzing followed by reflection. The results showed that the results from the initial data averaged only 73.6 with C (Enough) category. After action in Cycle I was taken by carrying out workshops and monitoring, it had increased to 80.93 with B (Good) category. The results of the workshop and monitoring actions in Cycle II by carrying out various innovations were able to increase the ability of teachers to an average of 91.2 with A (Very Good) category. These results have proven the success of the research conducted thus it can be concluded that workshops and monitoring were able to improve the ability of teachers in assisted vocational schools in carrying out the learning process using project-based learning model. These results have proven that the hypotheses presented can be accepted and the increase in results was in accordance with the indicators of research success.Keywords: workshop, monitoring, teacher’s ability to carry out the learning process, project-based learning model.